Anthropogenic activity in the Halifax region, Nova Scotia, Canada, as recorded by bulk geochemistry of lake sediments. (2nd October 2018) - Dunnington, Dewey W.; Spooner, Ian S.; Krkošek, Wendy H.; Gagnon, Graham A.; Cornett, R. Jack; Kurek, Joshua; White, Chris E.; Misiuk, Ben; Tymstra, Drake
ABSTRACT: Dunnington DW, Spooner IS, Krkošek WH, Gagnon GA, Cornett RJ, Kurek J, White CE, Misiuk B, Tymstra D. 2018. Anthropogenic activity in the Halifax region, Nova Scotia, Canada, as recorded by bulk geochemistry of lake sediments. Lake Reserv Manage. 34:334–348. Separating the timing and effects of multiple watershed disturbances is critical to a comprehensive understanding of lakes, which is required to effectively manage lacustrine systems that may be experiencing adverse water quality changes. Advances in X-ray fluorescence (XRF) technology has led to the availability of high-resolution, high-quality bulk geochemical data for aquatic sediments, which in combination with carbon, nitrogen, δ 13 C, and δ 15 N have the potential to identify watershed-scale disturbance in lake sediment cores. We integrated documented anthropogenic disturbances and changes in bulk geochemical parameters at 8 lakes within the Halifax Regional Municipality (HRM), Nova Scotia, Canada, 6 of which serve as drinking water sources. These data reflect more than 2 centuries of anthropogenic disturbance in the HRM that included deforestation, urbanization and related development, and water-level change. Deforestation activity was documented at Lake Major and Pockwock Lake by large increases in Ti, Zr, K, and Rb (50–300%), and moderate increases in C/N (>10%). Urbanization was resolved at Lake Fletcher, Lake Lemont, and First Lake by increases in Ti, Zr, K, and Rb (10–300%), decreases in C/N (>10%), and increases in δ 15 N (>2.0‰). These data broadly agree with previous paleolimnological bioproxy data, in some cases identifying disturbances that were not previously identified. Collectively these data suggest that bulk geochemical parameters and lake sediment archives are a useful method for lake managers to identify causal mechanisms for possible water quality changes resulting from watershed-scale disturbance.